Scared of the dark - Alexander, Liza.; Cooke, Tom; Children$1 (Bs Television Workshop.s ([New York] : Western Pub. Co. in conjunction with Children$1 (Bs Television Workshop,s, 1986)
After watching a scary movie, Ernie is afraid to go to sleep.
"Featuring Jim Henson$1 (Bs Sesame Street Muppets."s
"A Sesame Street/Golden Press book."
"A Golden book"--Cover.
Keywords: Night -- Fiction; Fear -- Fiction; Bedtime -- Fiction; Puppets -- Fiction